Using Edmodo as Web 2.0 Media for Teaching English in Higher Education: A Literature Review - Reftyawati, Dian (Lentera: Jurnal Ilmiah Kependidikan, 2022)
Writing as a productive skill in an EFL classroom is very important. In the writing class there needs to be an efficient relationship between teachers and students. In the early part of the 21st Century the various technologies available for use in the classroom have become extremely diverse and the way they are used in classrooms around the world may affect the outcomes we expect from our classrooms. This paper aims to examine the effectiveness of Edmodo in teaching writing to EFL students. Thus this review reports five relevant studies which] clearly indicated that Edmodo is an effective medium for teaching writing to EFL learners. The purpose of this review is to report: 1). Students' perceptions about the use of Edmodo in teaching writing for EFL students. 2). Edmodo benefits in teaching writing for EFL students. 3). Edmodo's shortcomings in teaching writing for EFL students. According to the findings, learning to use Edmodo on EFL students is very effective for improving writing skills in EFL students.